Cocktail Management of Flabby Tissue Using Window Technique with Glycerine Injected Prosthesis- A Case Report - Mishra, K; Hegde, D; Shetty, S; Vijayalakshmi, C R; Shah, S (Journal of Nepalese Prosthodontic Society, 2020)
Flabby ridge is an area of moveable soft tissue disturbing the maxillary or mandibular alveolar ridges. In this case, a technique for fabrication of a complete denture prosthesis is explained in which window technique has been used for making a secondary impression in the area of flabby tissue and then glycerine-supported denture fabrication was carried out which eliminates the disadvantages of tissue conditioners and soft liners and preserves the remaining tissues.